If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + (-3) = -8 n + -3 = -8 Reorder the terms: -3 + n = -8 Solving -3 + n = -8 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + n = -8 + 3 Combine like terms: -3 + 3 = 0 0 + n = -8 + 3 n = -8 + 3 Combine like terms: -8 + 3 = -5 n = -5 Simplifying n = -5
| 4(6y-5)=220 | | b/5=-4/7 | | 2(4d-1)=22 | | 43/9=m+4 | | n/-7=4/7 | | x-1/5=29/5 | | x+1/5=51/5 | | 4(b-3)=64 | | 3(c+7)=30 | | 8/9+x=44/9 | | m+2/5=24/35 | | b/7=4 | | k-6/7=8/7 | | 65/6=a-1/6 | | t/-3=5 | | -3/7n=36/7 | | -1/2d=-1/2 | | 1/4b=1/7 | | n+2/7=86/7 | | a-2/3=-2/3 | | -8+n=-65/9 | | -16x^2+96x+256=0 | | n-1/2=13/2 | | 44/7=a+7 | | -7k=28/11 | | x+2/5=42/5 | | -n=-5 | | d/2=-5 | | 2b=5/3 | | d+1/3=-23/3 | | -7/4=n-3/4 | | w+8/9=49/45 |